2012
DOI: 10.1186/1471-2407-12-248
|View full text |Cite
|
Sign up to set email alerts
|

SOXs in human prostate cancer: implication as progression and prognosis factors

Abstract: BackgroundSOX genes play an important role in a number of developmental processes. Potential roles of SOXs have been demonstrated in various neoplastic tissues as tumor suppressors or promoters depending on tumor status and types. The aim of this study was to investigate the involvement of SOXs in the progression and prognosis of human prostate cancer (PCa).MethodsThe gene expression changes of SOXs in human PCa tissues compared with non-cancerous prostate tissues was detected using gene expression microarray,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
44
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 26 publications
5
44
0
2
Order By: Relevance
“…Recent studies have shown the involvement of upregulated SOX9 in several cancer types [5,[10][11][12][13], including lung adenocarcinoma, breast carcinoma, colorectal cancer, and PCa. Furthermore, our previous study reported the association of increased serum level of SOX9 with aggressive tumor progression and poor prognosis in PCa patients, thereby suggesting its potential as a serological tumor marker for PCa [14,15]. However, the clinical and functional significance of SOX9 expression has not yet been characterized in other urological cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown the involvement of upregulated SOX9 in several cancer types [5,[10][11][12][13], including lung adenocarcinoma, breast carcinoma, colorectal cancer, and PCa. Furthermore, our previous study reported the association of increased serum level of SOX9 with aggressive tumor progression and poor prognosis in PCa patients, thereby suggesting its potential as a serological tumor marker for PCa [14,15]. However, the clinical and functional significance of SOX9 expression has not yet been characterized in other urological cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Sox10 was found downregulated in prostate carcinoma tissue compared to benign prostate tissue. In prostate carcinoma, low immunoreactivity of Sox10 was associated with high PSA level and advanced pathological stage [19]. Clearly, the role of Sox10 in oncogenesis of epithelial tumors needs to be further elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Sox10 reportedly functions as an oncogene by cell cycle dysregulation in melanomagenesis [18], and by activating the Wnt/β-catenin cascade in hepatocellular carcinoma [17]. In contrast, Sox10 is silenced or downregulated in prostatic carcinoma [19] and in gastrointestinal cancer [20], suggesting that in these tumors, it might function as a tumor suppressor.…”
Section: Introductionmentioning
confidence: 90%
“…In the study by Mohamed et al, 1 nonspecific background staining was observed in photomicrographs in both melanoma and in breast cancer. In a study by Zhong et al, 19 SOX10 was strongly positive in the cytoplasm of benign prostate tissue and was weakly positive in the cytoplasm of prostate cancer tissues. In our study, the new monoclonal SOX10 antibody produced clean nuclear staining with essentially no background staining.…”
mentioning
confidence: 99%
“…1,[10][11][12][13][14][15]19 The use of a research use-only goat primary antibody may be satisfactory for research purposes; however, it may not be generally accepted in a clinical setting. Polyclonal antibodies are also notorious for lot-to-lot variation and may produce unwanted nonspecific background staining.…”
mentioning
confidence: 99%